Measuring mental wellbeing in children aged 5 to 12 years: validation of the COMPAS-KIDS and COMPAS-PARENTS mental wellbeing scales in the general community - Lam, Janine R.; Gatt, Justine M. (Frontiers in Psychiatry, 2025)
IntroductionThe ever-rising incidence of mental health issues in children and adolescents is becoming an issue of global concern. One way to tackle this is to track mental wellbeing during development given the critical role of mental wellbeing within mental health more broadly. Unfortunately, there are limited comprehensive measures of mental wellbeing validated for child self-report, particularly in younger age groups.MethodsThree versions of the COMPAS-W mental wellbeing scale for adults was transformed for use in children and parents: The COMPAS-KIDS for children aged 5–7 years (21 items), COMPAS-KIDS for children aged 8–12 years (22 items), and the COMPAS-PARENTS for parents to report on their child’s mental wellbeing (22 items). These scales were validated in 99 children aged 5–7 years (n=43) and 8–12 years (n=56), and their parents.ResultsInternal reliability was demonstrated for the COMPAS-KIDS scale in children aged 5–7 years (a=0.664) and 8–12 years (a=0.784), and for the COMPAS-PARENTS scale in parents of children aged 5–7 years (a=0.819) and 8–12 years (a=0.861). Test-retest reliability demonstrated good stability over 4–6 weeks for the COMPAS-KIDS scale in children aged 5–7 years (r=0.769) and 8–12 years (r=0.910), and for the COMPAS-PARENTS scale in parents of children aged 5–7 years (r=0.859) and 8–12 years (r=0.901). Criterion validity was established in all age groups, with positive associations found between COMPAS, the PedsQL quality of life scale, the School Wellbeing scale, and negative associations with the CALIS anxiety scale. Correlations between child and parent scores showed some divergence in means, suggesting a reliance on parent report alone is not sufficient to capture child wellbeing. DiscussionThe COMPAS-KIDS and COMPAS-PARENTS scales are reliable and valid measures of mental wellbeing for children aged 5 to 12 years. The collection of surveys from both child and parent are recommended when measuring mental wellbeing. Future studies could consider validation of the scales in independent cohorts that include both clinical and non-clinical cohorts.